Comparative Study between Conventional and Islamic Banks during Pandemic Covid-19 - Putri Reno Kemala Sari; Eka Septriannisa; Nuwailah Nuwailah (Sekolah Tinggi Ilmu Ekonomi AMM, 2022)
The banking industry is one of the financial industries that plays a very important role in maintaining the stability of the Indonesian economy. Since the COVID-19 outbreak, economic activity has caused many individuals to wonder how Indonesia's banking sector is doing. The purpose of this study is to compare the credit resilience of Islamic and conventional banks. A dummy multiple regression analysis is the analysis technique utilized to compare the COVID-19 pandemic's pre and post-epidemic conditions. CAR, FDR/LDR, NPF/NPL, and COVID-19 pandemic as a dummy are the variables employed. Islamic and conventional banking firms listed on the Indonesian Stock Exchange make up the study's population. The COVID-19 pandemic dummy variable and the FDR variable, however, have a marginally minor effect on Islamic banking. The COVID-19 and CAR are having a major and favorable impact on conventional banking